2007
DOI: 10.1007/s11284-007-0429-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthropogenic disturbances on the butterfly assemblage in an urban green area: the changes from 1990 to 2005 in Kanazawa Castle Park, Japan

Abstract: Kanazawa Castle Park (KCP) is an isolated urban green area in Kanazawa, Japan. A mature forest had developed there since 1949, but it was partially deforested from 1996 to 1999. Moreover, most of the grasslands in KCP were removed from 2000 to 2002. In this study, we report the damage to the butterfly assemblage by these anthropogenic disturbances and subsequent recovery after the disturbances, using previous literature on the butterfly assemblage in KCP from 1990 to 1994 and our monitoring data from 1999 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Indeed, Öckinger, Dannestam, and Smith (2009) showed that early successional biotopes can accommodate high butterfly species richness in an urban environment. Ohwaki, Tanabe, and Nakamura (2008) also found that early successional grassland species recovered faster from anthropogenic disturbance in an urbanized area than late successional forest species. Altogether, our study shows that urban environments (in this case: existing business sites) may provide habitat for different butterfly species, including habitat specialists (of early-successional vegetation).…”
Section: Business Site Habitats As a Promising New Direction In Buttementioning
confidence: 80%
“…Indeed, Öckinger, Dannestam, and Smith (2009) showed that early successional biotopes can accommodate high butterfly species richness in an urban environment. Ohwaki, Tanabe, and Nakamura (2008) also found that early successional grassland species recovered faster from anthropogenic disturbance in an urbanized area than late successional forest species. Altogether, our study shows that urban environments (in this case: existing business sites) may provide habitat for different butterfly species, including habitat specialists (of early-successional vegetation).…”
Section: Business Site Habitats As a Promising New Direction In Buttementioning
confidence: 80%
“…P. xuthus was observed in all urban parks of various sizes (2.0-126 ha) in and around Osaka City, Japan (Imai 1998). P. xuthus did not decrease during the grassland removal and deforestation period in Kanazawa Castle Park, Japan (Ohwaki et al 2008). It is thought that P. xuthus may tolerate disturbances by humans because this species has a high dispersal ability and a broad range of food resources.…”
Section: Discussionmentioning
confidence: 95%
“…Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009). …”
Section: Discussionmentioning
confidence: 99%